PERKEMBANGAN TOKO MAINAN ANIME DAN TOKUSATSU JEPANG DI YOGYAKARTA - , HERU WIDIATMOKO; , Dr. Tatang Hariri, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This graduation paper presents the existence of shops which sell anime and tokusatsu character figure toys in Yogyakarta. The aim of this graduation paper writing is to explain the efforts made by the shopsâ owners in maintaining the existence of the shops in Yogyakarta from 2007 to 2012. In this paper, the researcher also presents some factors that support the shopsâ existence until 2012. The researcher uses Talcott Parsons model called âthe unit actâ to analyze the efforts and the factors that support the shopsâ existence. It is a model that says when someone is doing something